Improving Teacher Performance in Developing Teaching Materials Through Academic Supervision as an Effort to Improve Academic Quality in Schools - Mahsun Alwa'id (Universitas Veteran Bangun Nusantara, 2021)
An important problem that is often faced by teachers in learning activities is choosing or determining appropriate learning materials or teaching materials in order to help students achieve competence. This is due to the fact that in the curriculum or syllabus, teaching materials are only written in outline in the form of